Palestinians in Exile: Home and Identity in Abulhawa’s Against the Loveless World - Alwuraafi, Ebrahim (Contextos: Estudios de Humanidades y Ciencias Sociales, 2025)
Susan Abulhawa’s novels Against the Loveless World captures the experience of the Palestinians living in exile following their expulsion from their homeland. This article examines the identity of Palestinians living in exile as depicted in Abulhawa’s novel. A central focus of the analysis is how the novel challenges essentialist notions of identity as a fixed and stable construct. Through the experiences of the protagonist Nahr, a Palestinian exile, the article demonstrates that identity is fluid and dynamic, rather than static or fixed and constantly in flux, shaped and reshaped by the shifting contexts of displacement and diaspora. It argues that Nahr’s identity emerges from the interstitial spaces between cultures, histories, and geographies and that Nahr’s sense of self is not a monolithic or unitary entity, but rather a multilayered and ever-evolving amalgamation of her Palestinian roots, her experiences of exile, and the cultural influences she encounters in her host countries.